Corneal Topography: Sirius - Jigyasa Sahu (Delhi Journal of Ophthalmology)
Present-day corneal tomography analysis has improved accuracy of corneal contour detection and is considered extremely valuable in the diagnosis of subclinical keratoconus. Sirius (Costruzione Strumenti Oftalmici, Florence, Italy) based on a single Scheimpflug camera with Placido imaging, is one of the commonly used corneal tomography systems. It creates 3-D imaging of the anterior segment and provides details of the anterior and posterior corneal contour, pachymetry, anterior chamber depth, and pupil diameter. This article will help the clinician understand different indices of topography scan and will guide the practicing clinician by giving practical tips for decision-making in the diagnosis and management of keratoconus.